Web-Based System For "Pendaftaran Kursus Luar Julat" (E-Kulat) - Nurul Jannah, Buang (Universiti Malaysia Sarawak, (UNIMAS), 2015)
E-KULAT System is a web-based system for "Pendaftaran Kursus Luar Julat" that will he used by students of Software Engineering program of Faculty Science Computer and Information Technology. This system will help the process of "Pendaftaran Kursus Luar Julat" faster and easier. Currently this process is done manually, by using paper-based system where student needs to fill -in the form and submit it to the faculty for approval. At the same time, it is hard for student to backtrack the status of the application. With this system, it will help both students and related faculty staffs in handling the process of the application easily.